Untangling the Web of Systemic Autoinflammatory Diseases - Donato Rigante; Giuseppe Lopalco; Antonio Vitale; Orso Maria Lucherini; Francesco Caso; Caterina De Clemente; Francesco Molinaro; Mario Messina; Luisa Costa; Mariangela Atteno; Franco Laghi-Pasini; Giovanni Lapadula; et al. (Mediators of Inflammation)
The innate immune system is involved in the pathophysiology of systemic autoinflammatory diseases (SAIDs), an enlarging group of disorders caused by dysregulated production of proinflammatory cytokines, such as interleukin-1β and tumor necrosis factor-α, in which autoreactive T-lymphocytes and autoantibodies are indeed absent. A widely deranged innate immunity leads to overactivity of proinflammatory cytokines and subsequent multisite inflammatory symptoms depicting various conditions, such as hereditary periodic fevers, granulomatous disorders, and pyogenic diseases, collectively described in this review. Further research should enhance our understanding of the genetics behind SAIDs, unearth triggers of inflammatory attacks, and result in improvement for their diagnosis and treatment.